Potencial de estocagem subterrânea de gás natural em cavernas de sal abertas por dissolução em domo salino offshore no Brasil - Costa, Pedro Vassalo Maia da (2018)
This thesis evaluates the potential of underground natural gas storage (UGS) in salt caverns opened by dissolution in offshore salt domes in Brazil. In order to select the area, geological and logistic aspects are analyzed to determine the feasibility of the development of the technology. Currently, Brazil doesn’t have an UGS facility coupled to its natural gas (NG) distribution network, even though it has favorable geology and has several justifications for its implementation. As demonstrated in this thesis, there are several benefits that justify the introduction of this technology in the Brazilian natural gas distribution network. The NG thermals are gradually increasing their importance in the Brazilian electricity generation matrix and represent approximately 34,5% of the Brazilian consumption (EPE-BEN, 2017). This consumption is seasonal, inconsistent and increasingly unpredictable. In order to meet this demand, Brazil uses LNG carriers as contingent inventories. This contingency storage is very expensive. This thesis demonstrates the potential to storage NG in salt caverns in an offshore environment in Brazil, carrying out a market, strategic, logistic and a technological analysis to demonstrate its technical feasibility. The offshore salt deposits analyzed were the salt dome discovered by the exploratory well ESS-01, in the Espirito Santo basin, located 50 km from the Brazilain coast, with 50 m water depth. The salt dome comprises the construction of 14 giant caverns with 450 m of height and 150 m of diameter. Two caves operating together allow the maneuver of 918.852.550 m 3 of NG, equivalent to about 22 LNG ships, with the same objective. If all its potential for building caverns is exploited in the selected area, a total volume of working gas of approximately 13 billion m 3 of NG can be achieved.